Draft Sequencing Crested Wheatgrass Chromosomes Identified Evolutionary Structural Changes and Genes and Facilitated the Development of SSR Markers - Zwyrtková, Jana; Blavet, Nicolas; Doležalová, Alžběta; Cápal, Petr; Said, Mahmoud; Molnár, István; Vrána, Jan; Doležel, Jaroslav; Hřibová, Eva (International journal of molecular sciences, 2022)
Crested wheatgrass (Agropyron cristatum), a wild relative of wheat, is an attractive source of genes and alleles for their improvement. Its wider use is hampered by limited knowledge of its complex genome. In this work, individual chromosomes were purified by flow sorting, and DNA shotgun sequencing was performed. The annotation of chromosome-specific sequences characterized the DNA-repeat content and led to the identification of genic sequences. Among them, genic sequences homologous to genes conferring plant disease resistance and involved in plant tolerance to biotic and abiotic stress were identified. Genes belonging to the important groups for breeders involved in different functional categories were found. The analysis of the DNA-repeat content identified a new LTR element, Agrocen, which is enriched in centromeric regions. The colocalization of the element with the centromeric histone H3 variant CENH3 suggested its functional role in the grass centromere. Finally, 159 polymorphic simple-sequence-repeat (SSR) markers were identified, with 72 of them being chromosome- or chromosome-arm-specific, 16 mapping to more than one chromosome, and 71 mapping to all the Agropyron chromosomes. The markers were used to characterize orthologous relationships between A. cristatum and common wheat that will facilitate the introgression breeding of wheat using A. cristatum.
Keywords: Agropyron cristatum; Triticum; Illumina sequencing; chromosome sorting; chromozomy rostlin; pšenice; šlechtění rostlin; Agropyron; chromosome-specific sequences; Plant Breeding; Chromosomes, Plant; Disease Resistance; annotation; SSR-marker development; odolnost vůči nemocem